Enteric Viruses in Aquatic Environments - Haramoto, Eiji (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue contains one review and five original articles, all of which address cutting-edge research in the field of water and environmental virology. The review article by Gerba and Betancourt summarizes the current status and future needs for the development of virus detection methods in water reuse systems, especially focusing on methods to assess the infectivity of enteric viruses. Original papers cover a variety of research topics, such as an environmental monitoring survey of group A rotaviruses in sewage and oysters in Japan, the occurrence and genetic diversity of noroviruses and rotaviruses in a wastewater reclamation system in China, the detection of viruses and their indicators in tanker water and its sources in Nepal, integrated culture next-generation sequencing to identify the diversity of F-specific RNA coliphages in wastewater, and the development of a portable collection and detection method for viruses from ambient air and its application to a wastewater treatment plant.